2019
DOI: 10.1101/mcs.a003640
|View full text |Cite
|
Sign up to set email alerts
|

Identification of aggressive Gardner syndrome phenotype associated with a de novo APC variant, c.4666dup

Abstract: Gardner syndrome describes a variant phenotype of familial adenomatous polyposis (FAP), primarily characterized by extracolonic lesions including osteomas, dental abnormalities, epidermal cysts, and soft tissue tumors. We describe a 2-yr-old boy presenting with a 2-cm soft tissue mass of the forehead. Pathologic evaluation revealed a nuchal-type/Gardner-associated fibroma. Sequencing of the APC gene revealed a pathologic variant c.4666dupA. Parental sequencing of both blood and buccal ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 24 publications
(31 reference statements)
1
13
0
1
Order By: Relevance
“…described a patient with GS and a de novo APC mutation who developed multiple painful soft tissue tumors, though only the painless index lesion on the forehead was excised and on histology showed a typical GF with a predominant fibrous component. 3…”
Section: Discussionmentioning
confidence: 99%
“…described a patient with GS and a de novo APC mutation who developed multiple painful soft tissue tumors, though only the painless index lesion on the forehead was excised and on histology showed a typical GF with a predominant fibrous component. 3…”
Section: Discussionmentioning
confidence: 99%
“…Most nuchal-type fibromas arose in the posterior neck (2-9, 11-18, 23). However, other anatomic sites of origin were also reported less frequently, such as the back (3,5,(20)(21)(22) chest (20,21), shoulder (5,19,22,27,30,32), scapula (2,5,19), thigh (21), buttock (25,31), scalp (3,21,26), sacral region (28), mouth floor (33), eyebrow (29) and coccyx (23) ( Table I). A nuchal-type fibroma usually presents itself as a subcutaneous, soft-tissue, firm mass (3, 5, 6, 8, 12-19, 21, 25, 29, 32) that can be fixed or mobile (6,8,11,14,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) and painless or mildly tender (1, 3, 4, 7, 14, 16-19, 21, 24-28, 31, 33) (Table II) (Table III).…”
Section: Resultsmentioning
confidence: 99%
“…[31][32][33]. Two articles reported that a nuchal-type fibroma was depicted as a hypoechoic mass during a diagnostic ultrasound (17,29). Moreover, another article reported a nuchal-type fibroma with high density and two articles reported wellcircumscribed masses on computed tomography (9,29,33).…”
Section: Microscopic View Of the Surgical Specimen A: Thick Haphamentioning
confidence: 99%
See 2 more Smart Citations